Erythema Ab igne in an adolescent with anorexia nervosa. Issue 4 (15th November 2012) - Docx, Martine K.F.; Simons, Annik; Ramet, José; Mertens, Luc
Abstract Objective: A rare skin lesion, erythema ab igne (EAI) is presented, in an adolescent female with anorexia nervosa. Method: Clinical records of this patient were compared with a pubmed search about EAI in patients with an eating disorder. Results: The patient presented with localized, spider‐like, erythematous and hyperpigmented skin lesions on the lower abdomen and on both thighs. Repetitive exposure to heating pads can induce reticular and macular hyperpigmentation with telangiectases without squamation. Strict avoidance of heat is advised, because there is no effective treatment. Discussion: EAI is described in patients with an eating disorder. Facing an increased pain threshold, prolonged heat exposure to treat a general feeling of cold, can induce this dermatosis. © 2012 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)